An Unusual Presentation of Insert Dislocation and MCL Rupture in Unicompartmental Knee Replacement with 2 Years Postoperative Results: Does It Functional? - Ali Asma; Mehmet Erduran; Musa Eymir (Case Reports in Orthopedics)
According to our knowledge, there is no prior article that reports functional results of medial collateral ligament (MCL) primary repair and insert change after MCL rupture and mobile-bearing dislocation as a late complication of unicompartmental knee replacement (UKR). Firstly, 63-year-old woman was treated with UKR due to anteromedial knee osteoarthritis of the right knee joint. 1 year after UKR surgery, she suffered from MCL rupture and mobile-bearing dislocation because of falls while getting on a public bus, and therefore, secondly, she was operated with MCL primary repair and mobile-bearing change and followed up for 2 years. The patient was evaluated regarding functional capacity, pain intensity, range of motion (RoM), and quality of life. Our case showed an improvement in the functional level and the other outcomes (pain intensity and quality of life) at postoperative 2nd year when compared to the preoperative period. The wellbeing of our case in about the postop 2nd year functional capacity and also other outcomes after revision surgery prompted us to continue to this surgery approach in the surgical management of similar cases that may arise thereafter.